Farm management in West Africa - Phillips T.A. (London : Longman Group Limited, 1961)
This book gives the African farmer some assistance with his farm organisation and management, and thereby increase the profitability of his business.
Associated companies, branches and representatives throughout the world.
Includes index
uaa 25/01/19
Loans.
Keywords: Agriculture; Farm management; Africa, West; Africa